Investigating the Role of Smart Safety Systems in Mitigating Accident Rates Across High-Rise Construction Sites - Rifdah Wardani; Alfiah Ramadhani Amran; Rini Damayanti; A. Ferina Herbourina Bonita; Vina Levia Budiman (CV. Get Press Indonesia, 2025)
The high-rise construction sector faces major occupational safety risks (falls, struck-by incidents, equipment failure), resulting in significant losses. This study examines how smart safety systems (sensor helmets, IoT monitoring, drones, and AI prediction) mitigate these accident rates. Using a quantitative design and secondary data from global safety bodies and large contractors, the research analyzes incident reports and performance metrics via statistics and logistic regression. Results confirm a substantial accident rate reduction (over 50%) after smart system deployment, suggesting improved risk management and safety culture. Findings advocate for regulatory standards mandating smart safety technology integration. The conclusion underscores smart safety's transformative impact on construction safety and recommends further longitudinal study into adoption challenges and technological refinement.